Defense spending for Europe's security: How much is enough? - Florian Dorn (CESifo GmbH, 2024)
Defense spending above the NATO target of 2 percent of gross domestic product would be necessary for Europe to be able to defend itself without the protective umbrella of the United States. This is the conclusion of the new EconPol Policy Brief. European countries would have to significantly increase their efforts to catch up with an adequate defense capability, as defense budgets and military investments have been too low for years. Europe must compensate for higher real military costs than, for example, in Russia or China.
Keywords: 330